2023
DOI: 10.30632/pjv64n2-2023a5
|View full text |Cite
|
Sign up to set email alerts
|

An Unsupervised Machine-Learning Workflow for Outlier Detection and Log Editing With Prediction Uncertainty

Abstract: Recent advances in data science and machine learning (ML) have brought the benefits of these technologies closer to the mainstream of petrophysics. ML systems, where decisions and self-checks are made by carefully designed algorithms, in addition to executing typical tasks such as classification and regression, offer efficient and liberating solutions to the modern petrophysicist. The outline of such a system and its application in the form of a multilevel workflow to a 59-well multifield study are presented i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Petrophysics is a crucial discipline for determining the characteristics of reservoirs and developing new fields. Improved drilling efficiency, data repair, reservoir property prediction, reservoir rock type, and other petrophysics-related tasks have all benefited from the use of ML. , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Petrophysics is a crucial discipline for determining the characteristics of reservoirs and developing new fields. Improved drilling efficiency, data repair, reservoir property prediction, reservoir rock type, and other petrophysics-related tasks have all benefited from the use of ML. , …”
Section: Resultsmentioning
confidence: 99%
“…Within the geoscience domain, the adoption of ML algorithms such as the tree-based approach dates to the early 1960s . Machine-learning applications within petrophysics include the prediction of reservoir properties, , outlier detection, prediction of missing acoustic slowness, and well log repair. ,, Within the petrophysical workflow, data quality assurance is an important step and can take up a significant amount of time within a project. Friedman and Smith identified that poor data quality leads up to a 20% reduction in labor productivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Random forest is a popular machine-learning algorithm developed by Breiman (2001) and has been successfully used in various classification and regression problems (Akkurt et al 2018). The algorithm works by creating a large number of decision trees from bootstrap samples of the training data.…”
Section: Random Forest (Rf)mentioning
confidence: 99%